Assessment of Genetic Variability among Onion (Allium cepa L.) Cultivars using RAPD and SRAP Molecular Markers (University of Khartoum Journal of Agricultural Sciences, 2021)
Onion (Allium cepa L.) is one of the most important vegetable crops worldwide, however, limited studies are available on genetic variability of onion resources. The aim of this study was to assess the genetic diversity of twelve onion cultivars which are widely grown in different regions of Sudan, using RAPD and SRAP markers. A total of 32 RAPD and 21 SRAP primers were screened. To assess variability, the data generated were used to group the cultivars using Jaccard’s coefficient of similarity. Only 20, out oftested RAPD primers were producible and showed 326 different-sized DNA fragments with one or more of the tested cultivars giving an average of 27.17 alleles per cultivar. Hundred percent polymorphism was recorded for each of the primers tested with high polymorphism information content (PIC) ranging from 0.89 to 1.00. In SRAP analysis, 8 out of 21 primer pairs tested,produced bands of different sizes. A total of 66 DNA fragments were detected for the 12 cultivars with an average of 5.5 alleles per cultivar. The number of different fragments generated by each primer ranged from one to eight and 100 percent polymorphism was recorded for each of the primers tested with high PIC of approximately 1.00. Similarity matrices constructedusing RAPD, SRAP or the combined data suggested a relatively high level of genetic diversity among the 12 onion cultivars, the most diverse cultivars were Shendi yellow and Baftaim red hybrid with 14 % similarity. The study revealed that although both molecular markers used were efficient in elucidating genetic diversity among the tested onion cultivars, SRAP markerswere the most potential and could be used as an integrated approach in onion breeding programmes.
Keywords: onion; Markers; genetic diversity; polymorphism